3D for graphic designers - Connell, Ellery , 1978- (John Wiley & Sons, 2011)
"Helping graphic designers expand their 2D skills into the 3D spaceThe trend in graphic design is towards 3D, with the demand for motion graphics, animation, photorealism, and interactivity rapidly increasing. And with the meteoric rise of iPads, smartphones, and other interactive devices, the design landscape is changing faster than ever.2D digital artists who need a quick and efficient way to join this brave new world will want 3D for Graphic Designers.Readers get hands-on basic training in working in the 3D space, including product design, industrial design and visualization, modeling, animation, lighting, and rendering?all the skills necessary in today?s competitive environment. Helps 2D graphic designers gain the skills they need for a competitive job market that increasingly demands the ability to create or work in 3D Covers product design, industrial design and visualization, modeling, animation, lighting, and rendering Prepares you to create designs for iPads and other interactive mobile devices, as well as for print, Web, broadcast, film, HD, video, and more Uses Luxology modo to illustrate 3D concepts, but the author?s techniques and insights will help any artist moving into 3D, no matter what software they use This timely book is just what you need to create compelling and realistic 3D imagery and improve your job skills"-- Provided by publisher